A method for preparing sodium niobate-based dielectric ceramics
Through the preparation method of sodium niobate-based dielectric ceramics, the problems of dielectric loss and heating in existing ferroelectric ceramics under high electric fields are solved, and the dielectric loss reduction and linear change in capacitance are achieved. It is suitable for electric field sensor applications with high electric field strength.
Patent Information
- Application Number
- CN202410970616.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-19
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-07-19
AI Technical Summary
Existing ferroelectric ceramics have high dielectric loss and heat generation under low application electric fields, which cannot meet the application needs of high electric field strength.
Sodium niobate-based lead-free dielectric ceramics are prepared by using the preparation method of sodium niobate-based dielectric ceramics, through dry press molding and process parameter optimization of powder material, and sodium niobate-based lead-free dielectric ceramics with linear variations with the applied electric field strength under a wide electric field strength range (0~105 kV/cm).
The dielectric loss reduction and good linear capacitance changes under high electric fields are achieved, and the dielectric loss is less than 0.005, which is suitable for the electric field sensor field that senses capacitance changes.
Smart Images

Figure CN118515482B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional ceramic materials, and in particular to a method for preparing sodium niobate-based dielectric ceramics. Background Art
[0002] Ferroelectric ceramics have the characteristics of high temperature stability and wide frequency response range. They can calibrate the external electric field strength by sensing the capacitance or volume changes under the action of the electric field. Electric field sensors with this type of dielectric material as the core have important and wide applications in many fields such as aerospace, smart grid, petrochemical and meteorological science research.
[0003] Data show that the current application electric field of most ferroelectric ceramics is low (≤30 kV / cm), which cannot meet the application requirements. At the same time, most electric field sensors based on ferroelectric ceramics have high dielectric loss and heat generation, which will bring a greater burden to other electronic components and increase energy consumption. Therefore, it is particularly necessary to develop a dielectric ceramic with a wide electric field range and low loss for the development of electric field sensors. Antiferroelectric materials usually have low loss (≤0.005) and high application electric field strength (≥80 kV / cm). It is feasible to improve material properties in antiferroelectric materials through composition design.
[0004] Chinese patent document CN117088687A discloses a "cubic sodium niobate ceramic dielectric material for ceramic capacitors and its preparation method". The cubic sodium niobate ceramic dielectric material, whose raw material group includes NaNbO3, BiZn0.5Ti0.5, and LiNiMnO, is modified by limiting the raw material composition and preparation method of cubic sodium niobate, adopting a multi-step grinding synthesis method to coordinate chemical structure modification, and controlling the grain morphology, size and dispersibility of the ceramic powder to improve the density of the porcelain body and the breakdown electric field strength; by adding BiZn0.5Ti0.5 and Li2NiMnO3 for chemical modification, the stability of the antiferroelectric phase is improved and the energy storage performance is optimized. The above technical solution lacks optimization of dielectric loss and applied electric field. Summary of the invention
[0005] The present invention mainly solves the technical problem that the original technical solution lacks optimization for dielectric loss and applied electric field, provides a method for preparing sodium niobate-based dielectric ceramics, utilizes the unique antiferroelectric properties of the material to regulate the electric field-capacitance properties of the dielectric ceramics, adopts a powder dry pressing molding method, optimizes process parameters such as sintering temperature, and prepares a sodium niobate-based lead-free dielectric ceramic whose capacitance changes linearly with the applied electric field strength in a wide electric field strength range (0-105 kV / cm). The dielectric ceramic can be applied to the field of electric field sensors that sense capacitance changes, and achieves optimization of dielectric loss and applied electric field.
[0006] The above technical problems of the present invention are mainly solved by the following technical solutions:
[0007] A method for preparing sodium niobate-based dielectric ceramics comprises the following steps:
[0008] S1 selects chemically pure raw materials according to the stoichiometric ratio of the sodium niobate-based dielectric ceramic chemical formula, mixes with an organic solvent, and ball-mills to obtain a slurry;
[0009] The chemical formula of the sodium niobate-based dielectric ceramic is (1-x)(Na 1-y K y )NbO3-xABO3;
[0010] Among them, A=Ca, Sr, Ba; B= Hf, Zr, Sn, Ti;
[0011] Said x and y In mole percentage, 0.03≤x≤0.15, 0.001≤y≤0.005;
[0012] S2 dries the slurry and sieves it, and grinds it to obtain a pre-burned powder after the initial heat preservation pre-burning;
[0013] S3: mixing the pre-burned powder with an organic solvent again, ball-milling to obtain a slurry, and then drying again to obtain a powder;
[0014] S4 cools the dried powder and isostatically presses it into a block, buries the mother powder, and performs secondary heat preservation sintering to obtain fired ceramics;
[0015] S5 grinds the fired ceramic into a thin layer and then polishes it, silver-plates both sides, and then sinters the silver-plated ceramic sheet three times under heat preservation.
[0016] Preferably, during the ball milling process of step S1 and step S3, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:4.
[0017] Preferably, the ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
[0018] Preferably, the drying process in step S2 and step S3 is carried out at 120° C., and the product in step S2 is passed through a 60-mesh sieve after drying.
[0019] Preferably, the initial heat preservation and pre-sintering in step S2 is specifically to place the steel into a heat treatment furnace and to pre-sinter at 700-900° C. for 4 hours.
[0020] Preferably, the secondary heat preservation pre-sintering in step S4 is specifically performed by heat preservation sintering in a sintering furnace at 1300-1400° C. for 2-4 hours.
[0021] Preferably, the three-times heat preservation pre-sintering in step S5 is specifically sintering in a sintering furnace at 400° C. for 0-30 minutes.
[0022] Preferably, the isostatic pressure of the isostatic pressing in step S4 is 200 MPa, and the holding time is 5 min.
[0023] Preferably, the ceramic fired in step S5 is ground to a thickness of 0.3 mm and then polished, and a silver layer with a thickness of 0.1±0.01 mm is plated on the surfaces of both sides of the ceramic disc. The silver-plated ceramic disc is cut into pieces with a volume of 3×3×0.3 mm 3 of blocks.
[0024] Preferably, the powder dried in step S4 is cooled and isostatically pressed into a cylindrical block, and in step S5 the fired ceramic is ground and polished, and silver-plated and sintered into silver-plated ceramic discs.
[0025] The beneficial effects of the present invention are: improving performance and optimizing process in antiferroelectric materials by controlling components, greatly reducing dielectric loss, having good linear capacitance change at high electric field, and utilizing the sodium niobate-based dielectric ceramics obtained by the present invention, the applied electric field can reach 0-105 kV / cm, the dielectric loss is lower than 0.005, the capacitance and loss have a wide frequency range response, and can be applied to the field of electric field sensors that sense capacitance changes, to achieve optimization of dielectric loss and applied electric field. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a flow chart of the present invention.
[0027] Figure 2 It is a ceramic cutting diagram of the present invention.
[0028] Figure 3 This is a relationship diagram between capacitance and applied electric field strength of the present invention.
[0029] Figure 4 It is a capacitance and dielectric loss versus frequency graph of the present invention. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the technical solution of the present invention is further described in detail below through embodiments and in combination with the accompanying drawings. It should be understood that the specific implementation method described here is only an optimal embodiment of the present invention, which is only used to explain the present invention and does not limit the scope of protection of the present invention. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] Before discussing the exemplary embodiments in more detail, it should be mentioned that some exemplary embodiments are described as processes or methods depicted as flow charts. Although the flow charts describe the operations (or steps) as sequential processes, many of the operations (or steps) therein can be implemented in parallel, concurrently, or simultaneously. In addition, the order of the operations can be rearranged. The process can be terminated when its operation is completed, but can also have additional steps not included in the drawings; the process can correspond to a method, function, procedure, subroutine, subprogram, etc.
[0032] Ferroelectric ceramics have the characteristics of high temperature stability and wide frequency response range. They can calibrate the external electric field strength by sensing the capacitance or volume changes under the action of the electric field. Electric field sensors with this type of dielectric material as the core have important and wide applications in many fields such as aerospace, smart grid, petrochemical and meteorological science research.
[0033] At present, the application electric field of most ferroelectric ceramics is low (≤30 kV / cm), which cannot meet the application requirements. At the same time, most electric field sensors based on ferroelectric ceramics have high dielectric loss and heat generation, which will bring a heavy burden to other electronic components and increase energy consumption. Therefore, it is particularly necessary to develop a dielectric ceramic with a wide electric field range and low loss for the development of electric field sensors. Antiferroelectric materials usually have low loss (≤0.005) and high application electric field strength (≥80 kV / cm). It is feasible to improve material properties in antiferroelectric materials through composition design.
[0034] In view of the above problems, the present invention proposes a sodium niobate-based lead-free dielectric ceramic whose capacitance changes linearly with the applied electric field strength and a preparation process thereof. The unique antiferroelectric properties of the material are used to regulate the electric field-capacitance properties of the dielectric ceramic. A powder dry pressing method is adopted, and process parameters such as sintering temperature are optimized to prepare a sodium niobate-based lead-free dielectric ceramic whose capacitance changes linearly with the applied electric field strength in a wide electric field strength range (0~105 kV / cm). The ceramic is expected to be applied in the field of electric field sensors that sense capacitance changes.
[0035] The technical solution of the present invention is further specifically described below through embodiments and in conjunction with the accompanying drawings.
[0036] Embodiment: In this embodiment, a sodium niobate-based lead-free dielectric ceramic whose capacitance varies with field strength has a general chemical formula of (1-x)(Na 1-y K y )NbO3-xABO3;
[0037] Among them, A=Ca, Sr, Ba; B= Hf, Zr, Sn, Ti;
[0038] Saidx and y In mole percentage, 0.03≤x≤0.15, 0.001≤y≤0.005.
[0039] Among them, the specific chemical formula exists in the following proportion forms, including:
[0040] 0.90(Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3;
[0041] 0.90(Na 0.998 K 0.002 )NbO3-0.097SrZrO3-0.003BaSnO3;
[0042] 0.90(Na 0.998 K 0.002 )NbO3-0.097SrHfO3-0.003BaZrO3.
[0043] A method for preparing a sodium niobate-based lead-free dielectric ceramic whose capacitance varies with field strength comprises the following steps:
[0044] S1: According to the metering ratio of the above specific chemical formula, chemically pure raw materials are selected and weighed, mixed with organic solvents, and ball-milled to obtain slurry. During the ball milling process, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:4. The ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
[0045] S2 dries the slurry and sieves it, grinds it after the initial heat preservation and pre-calcination to obtain the pre-calcined powder. The drying temperature is 120 ℃, and after drying, it is screened through a 60-mesh screen. The initial heat preservation and pre-calcination is specifically placed in a heat treatment furnace and heat-pre-calcined at 700-900 ℃ for 4 hours.
[0046] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3, put it into a heat treatment furnace and pre-sinter it at 850 ℃ for 4 h.
[0047] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrZrO3-0.003BaSnO3 was placed in a heat treatment furnace and pre-sintered at 850 ℃ for 4 h.
[0048] When the chemical formula is 0.90(Na 0.998 K 0.002)NbO3-0.097SrHfO3-0.003BaZrO3, put it into a heat treatment furnace and pre-sinter it at 850 ℃ for 4 h.
[0049] S3: Mix the pre-sintered powder with an organic solvent again, ball-mill to obtain a slurry, and then dry it again to obtain a powder. During the ball milling process, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:4. The ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
[0050] S4 cools the dried powder and isostatically presses it into a cylindrical block, buries the mother powder, and performs secondary heat preservation sintering to obtain fired ceramics. The isostatic pressure of medium static pressing is 200 MPa, and the holding time is 5 min. After cooling, isostatic pressure is applied again to ensure that the final cylindrical block has a uniform texture and can be effectively pre-sintered for secondary heat preservation. Specifically, the secondary heat preservation pre-sintering is sintered in a sintering furnace at 1300-1400 °C for 2-4 h.
[0051] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3 is sintered in a sintering furnace at 1345 ℃ for 2 h to obtain a sintered ceramic.
[0052] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrZrO3-0.003BaSnO3 is sintered in a sintering furnace at 1330 ℃ for 2 h to obtain a fired ceramic.
[0053] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrHfO3-0.003BaZrO3 is sintered in a sintering furnace at 1300 ℃ for 2 h to obtain a fired ceramic.
[0054] The ceramic raw materials obtained with different chemical formula ratios are placed in sintering furnaces at different temperatures for heat preservation and sintering, ensuring that the ceramic raw materials obtained with each chemical formula ratio can be effectively sintered into ceramics, so as to carry out the subsequent silver plating and cutting processes to ensure the integrity of the finished product.
[0055] S5 grinds the fired ceramic to a thin thickness and then polishes it, silver-plating both sides and then sintering it for three times to obtain a silver-plated ceramic disc. The fired ceramic is ground to a thin thickness of 0.3 mm and then polished, and a layer of silver with a thickness of 0.1±0.01 mm is plated on the surface of both sides of the ceramic disc. The three-times heat preservation pre-sintering is specifically, sintering in a sintering furnace at 400 ° C for 0-30 minutes to obtain a silver-plated ceramic disc.
[0056] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3 is sintered in a sintering furnace at 1345 ℃ for 2 h to obtain a sintered ceramic.
[0057] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrZrO3-0.003BaSnO3 is sintered in a sintering furnace at 1330 ℃ for 2 h to obtain a fired ceramic.
[0058] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrHfO3-0.003BaZrO3 is sintered in a sintering furnace at 1300 ℃ for 2 h to obtain a fired ceramic.
[0059] The silver-coated ceramic disc was cut into pieces with a volume of 3×3×0.3 mm 3 Ceramic cutting methods such as Figure 1 As shown in Figure 2, the lead-free dielectric ceramic can maintain a good linear change under an applied electric field strength of 105 kV / cm, with a linearity of 95%, and the capacitance and dielectric loss are within 10 3 -10 6 The loss is 0.003 at 10 kHz.
[0060] Embodiment 1:
[0061] A sodium niobate-based lead-free dielectric ceramic whose capacitance varies with field strength. The general chemical formula of the sodium niobate-based lead-free dielectric ceramic is (1-x)(Na 1-y K y )NbO3-xABO3;
[0062] Among them, A=Ca, Sr, Ba; B= Hf, Zr, Sn, Ti;
[0063] Said x and y In mole percentage, 0.03≤x≤0.15, 0.001≤y≤0.005.
[0064] Among them, the specific chemical formula can be in the following proportion form, and the specific chemical composition is: 0.90 (Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3, a method for preparing a sodium niobate-based lead-free dielectric ceramic whose capacitance varies with field strength, comprising the following steps:
[0065] S1: According to the metering ratio of the above specific chemical formula, chemically pure raw materials are selected and weighed, mixed with organic solvents, and ball-milled to obtain slurry. During the ball milling process, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:4. The ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
[0066] S2 dries the slurry and sieves it, grinds it after the initial heat preservation and pre-calcination to obtain the pre-calcined powder. The drying temperature is 120 ℃, and after drying, it is screened through a 60-mesh screen. The initial heat preservation and pre-calcination is specifically placed in a heat treatment furnace and heat-pre-calcined at 700-900 ℃ for 4 hours.
[0067] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3, put it into a heat treatment furnace and pre-sinter it at 850 ℃ for 4 h.
[0068] S3: Mix the pre-sintered powder with an organic solvent again, ball-mill to obtain a slurry, and then dry it again to obtain a powder. During the ball milling process, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:4. The ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
[0069] S4 cools the dried powder and isostatically presses it into a cylindrical block, buries the mother powder, and performs secondary heat preservation sintering to obtain fired ceramics. The isostatic pressure of medium static pressing is 200 MPa, and the holding time is 5 min. After cooling, isostatic pressure is applied again to ensure that the final cylindrical block has a uniform texture and can be effectively pre-sintered for secondary heat preservation. Specifically, the secondary heat preservation pre-sintering is sintered in a sintering furnace at 1300-1400 °C for 2-4 h.
[0070] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3 is sintered in a sintering furnace at 1345 ℃ for 2 h to obtain a sintered ceramic.
[0071] The ceramic raw materials obtained with different chemical formula ratios are placed in sintering furnaces at different temperatures for heat preservation and sintering, ensuring that the ceramic raw materials obtained with each chemical formula ratio can be effectively sintered into ceramics, so as to carry out the subsequent silver plating and cutting processes to ensure the integrity of the finished product.
[0072] S5 grinds the fired ceramic to a thin thickness and then polishes it, silver-plating both sides and then sintering it for three times to obtain a silver-plated ceramic disc. The fired ceramic is ground to a thin thickness of 0.3 mm and then polished, and a layer of silver with a thickness of 0.1±0.01 mm is plated on the surface of both sides of the ceramic disc. The three-times heat preservation pre-sintering is specifically, sintering in a sintering furnace at 400 ° C for 0-30 minutes to obtain a silver-plated ceramic disc.
[0073] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3 is sintered in a sintering furnace at 1345 ℃ for 2 h to obtain a sintered ceramic.
[0074] The silver-coated ceramic disc was cut into pieces with a volume of 3×3×0.3 mm 3 Ceramic cutting methods such as Figure 1 As shown in Figure 2, the lead-free dielectric ceramic can maintain good linear changes under an applied electric field strength of 0-105 kV / cm, with a linearity of 97.2%, and the capacitance and dielectric loss are within 10 3 -10 6 The loss is 0.001 at 10kHz.
[0075] Figure 2 and Figure 3 The capacitance of the sodium niobate-based ceramic varies with the electric field and the stability of the capacitance and dielectric loss over a wide frequency range. Figure 2 is the relationship between capacitance and applied electric field strength, Figure 3 Capacitance and dielectric loss vs. frequency graphs; Figure 2 and Figure 3 The added material composition is 0.90 (Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3.
[0076] Embodiment 2:
[0077] A sodium niobate-based lead-free dielectric ceramic whose capacitance varies with field strength. The general chemical formula of the sodium niobate-based lead-free dielectric ceramic is (1-x)(Na 1-y K y )NbO3-xABO3;
[0078] Among them, A=Ca, Sr, Ba; B= Hf, Zr, Sn, Ti;
[0079] Said x and y In mole percentage, 0.03≤x≤0.15, 0.001≤y≤0.005.
[0080] Among them, the specific chemical formula can be in the following proportion form, and the specific chemical composition is: 0.90 (Na 0.998 K 0.002 )NbO3-0.097SrZrO3-0.003BaSnO3, comprising the following steps:
[0081] A method for preparing a sodium niobate-based lead-free dielectric ceramic whose capacitance varies with field strength comprises the following steps:
[0082] S1: According to the metering ratio of the above specific chemical formula, chemically pure raw materials are selected and weighed, mixed with organic solvents, and ball-milled to obtain slurry. During the ball milling process, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:4. The ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
[0083] S2 dries the slurry and sieves it, grinds it after the initial heat preservation and pre-calcination to obtain the pre-calcined powder. The drying temperature is 120 ℃, and after drying, it is screened through a 60-mesh screen. The initial heat preservation and pre-calcination is specifically placed in a heat treatment furnace and heat-pre-calcined at 700-900 ℃ for 4 hours.
[0084] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrZrO3-0.003BaSnO3 was placed in a heat treatment furnace and pre-sintered at 850 ℃ for 4 h.
[0085] S3: Mix the pre-sintered powder with an organic solvent again, ball-mill to obtain a slurry, and then dry it again to obtain a powder. During the ball milling process, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:4. The ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
[0086] S4 cools the dried powder and isostatically presses it into a cylindrical block, buries the mother powder, and performs secondary heat preservation sintering to obtain fired ceramics. The isostatic pressure of medium static pressing is 200 MPa, and the holding time is 5 min. After cooling, isostatic pressure is applied again to ensure that the final cylindrical block has a uniform texture and can be effectively pre-sintered for secondary heat preservation. Specifically, the secondary heat preservation pre-sintering is sintered in a sintering furnace at 1300-1400 °C for 2-4 h.
[0087] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrZrO3-0.003BaSnO3 is sintered in a sintering furnace at 1330 ℃ for 2 h to obtain a fired ceramic.
[0088] The ceramic raw materials obtained with different chemical formula ratios are placed in sintering furnaces at different temperatures for heat preservation and sintering, ensuring that the ceramic raw materials obtained with each chemical formula ratio can be effectively sintered into ceramics, so as to carry out the subsequent silver plating and cutting processes to ensure the integrity of the finished product.
[0089] S5 grinds the fired ceramic to a thin thickness and then polishes it, silver-plating both sides and then sintering it for three times to obtain a silver-plated ceramic disc. The fired ceramic is ground to a thin thickness of 0.3 mm and then polished, and a layer of silver with a thickness of 0.1±0.01 mm is plated on the surface of both sides of the ceramic disc. The three-times heat preservation pre-sintering is specifically, sintering in a sintering furnace at 400 ° C for 0-30 minutes to obtain a silver-plated ceramic disc.
[0090] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrZrO3-0.003BaSnO3 is sintered in a sintering furnace at 1330 ℃ for 2 h to obtain a fired ceramic.
[0091] The silver-coated ceramic disc was cut into pieces with a volume of 3×3×0.3 mm 3 Ceramic cutting methods such as Figure 1 As shown in Figure 2, the lead-free dielectric ceramic can maintain a good linear change under an applied electric field strength of 105 kV / cm, with a linearity of 95%, and the capacitance and dielectric loss are within 10 3 -10 6 The loss is 0.003 at 10 kHz. Figure 2 and Figure 3 The capacitance of the sodium niobate-based ceramic varies with the electric field and the stability of the capacitance and dielectric loss over a wide frequency range. Figure 2 is the relationship between capacitance and applied electric field strength, Figure 3 Capacitance and dielectric losses versus frequency.
[0092] Embodiment 3:
[0093] A sodium niobate-based lead-free dielectric ceramic whose capacitance varies with field strength. The general chemical formula of the sodium niobate-based lead-free dielectric ceramic is (1-x)(Na 1-y K y )NbO3-xABO3;
[0094] Among them, A=Ca, Sr, Ba; B= Hf, Zr, Sn, Ti;
[0095] Said x and y In mole percentage, 0.03≤x≤0.15, 0.001≤y≤0.005.
[0096] Among them, the specific chemical formula can be in the following proportion form, and the specific chemical composition is: 0.90 (Na 0.998 K 0.002 )NbO3-0.097SrHfO3-0.003BaZrO3, comprising the following steps: A method for preparing a sodium niobate-based lead-free dielectric ceramic whose capacitance varies with field intensity, comprising the following steps:
[0097] S1: According to the metering ratio of the above specific chemical formula, chemically pure raw materials are selected and weighed, mixed with organic solvents, and ball-milled to obtain slurry. During the ball milling process, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:4. The ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
[0098] S2 dries the slurry and sieves it, grinds it after the initial heat preservation and pre-calcination to obtain the pre-calcined powder. The drying temperature is 120 ℃, and after drying, it is screened through a 60-mesh screen. The initial heat preservation and pre-calcination is specifically placed in a heat treatment furnace and heat-pre-calcined at 700-900 ℃ for 4 hours.
[0099] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrHfO3-0.003BaZrO3, put it into a heat treatment furnace and pre-sinter it at 850 ℃ for 4 h.
[0100] S3: Mix the pre-sintered powder with an organic solvent again, ball-mill to obtain a slurry, and then dry it again to obtain a powder. During the ball milling process, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:4. The ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
[0101] S4 cools the dried powder and isostatically presses it into a cylindrical block, buries the mother powder, and performs secondary heat preservation sintering to obtain fired ceramics. The isostatic pressure of medium static pressing is 200 MPa, and the holding time is 5 min. After cooling, isostatic pressure is applied again to ensure that the final cylindrical block has a uniform texture and can be effectively pre-sintered for secondary heat preservation. Specifically, the secondary heat preservation pre-sintering is sintered in a sintering furnace at 1300-1400 °C for 2-4 h.
[0102] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrHfO3-0.003BaZrO3 is sintered in a sintering furnace at 1300 ℃ for 2 h to obtain a fired ceramic.
[0103] The ceramic raw materials obtained with different chemical formula ratios are placed in sintering furnaces at different temperatures for heat preservation and sintering, ensuring that the ceramic raw materials obtained with each chemical formula ratio can be effectively sintered into ceramics, so as to carry out the subsequent silver plating and cutting processes to ensure the integrity of the finished product.
[0104] S5 grinds the fired ceramic to a thin thickness and then polishes it, silver-plating both sides and then sintering it for three times to obtain a silver-plated ceramic disc. The fired ceramic is ground to a thin thickness of 0.3 mm and then polished, and a layer of silver with a thickness of 0.1±0.01 mm is plated on the surface of both sides of the ceramic disc. The three-times heat preservation pre-sintering is specifically, sintering in a sintering furnace at 400 ° C for 0-30 minutes to obtain a silver-plated ceramic disc.
[0105] When the chemical formula is 0.90(Na 0.998 K 0.002 )NbO3-0.097SrHfO3-0.003BaZrO3 is sintered in a sintering furnace at 1300 ℃ for 2 h to obtain a fired ceramic.
[0106] The silver-coated ceramic disc was cut into pieces with a volume of 3×3×0.3 mm 3 Ceramic cutting methods such as Figure 1 As shown in Figure 2, the lead-free dielectric ceramic can maintain a good linear change under an applied electric field strength of 105 kV / cm, with a linearity of 94%, and the capacitance and dielectric loss are within 10 3 -10 6 The loss is 0.002 at 10 kHz. Figure 2 and Figure 3 The capacitance of the sodium niobate-based ceramic varies with the electric field and the stability of the capacitance and dielectric loss over a wide frequency range. Figure 2 is the relationship between capacitance and applied electric field strength, Figure 3 Capacitance and dielectric losses versus frequency.
[0107] Compared with the prior art, the present invention selects sodium niobate-based lead-free dielectric ceramics as the dielectric material of the electric field sensor, improves the performance and optimizes the process in the antiferroelectric material by component regulation, greatly reduces the dielectric loss, and has good linear capacitance change in high electric field. The sodium niobate-based dielectric ceramics obtained by the present invention can achieve an applied electric field of 0-105 kV / cm, the dielectric loss is less than 0.005, and the capacitance and loss have a wide frequency range response.
[0108] A person of ordinary skill in the art can understand that all or part of the steps in the various methods of the above embodiments can be completed by instructing related hardware through a program, and the program can be stored in a computer-readable storage medium, and the storage medium may include: a read-only memory (ROM), a random access memory (RAM), a disk or an optical disk, etc.
[0109] The specific embodiments described herein are merely examples of the spirit of the present invention. The above embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that technicians in the technical field to which the present invention belongs can make various modifications or supplements to the described specific embodiments or replace them in a similar manner, but will not deviate from the spirit of the present invention or exceed the scope defined in the attached claims. For ordinary technicians in this field, multiple deformations and improvements can also be made without departing from the concept of the present invention. Therefore, the scope of protection of the patent of the present invention shall be based on the attached claims.
Claims
1. A method for preparing sodium niobate-based dielectric ceramics, characterized in that: The following steps are involved: S1 selects chemically pure raw materials according to the stoichiometric ratio of the sodium niobate-based dielectric ceramic chemical formula, mixes with an organic solvent, and ball-mills to obtain a slurry. The chemical formula includes: 0.90(Na 0.998 K 0.002 )NbO3-0.095SrSnO3-0.005BaZrO3; 0.90(At 0.998 K 0.002 )NbO3-0.097SrZrO3-0.003BaSnO3; 0.90(At 0.998 K 0.002 )NbO3-0.097SrHfO3-0.003BaZrO3; S2 dries the slurry and sieves it, grinds it after the initial heat preservation sintering to obtain the pre-burned powder; S3: mixing the pre-burned powder with an organic solvent again, ball-milling to obtain a slurry, and then drying again to obtain a powder; S4 cools the dried powder and isostatically presses it into a block, buries the mother powder, and performs secondary heat preservation sintering to obtain fired ceramics; S5 grinds the fired ceramic into a thin layer and then polishes it, silver-plates both sides, and then sinters the silver-plated ceramic sheet three times under heat preservation.
2. The method for preparing sodium niobate-based dielectric ceramics according to claim 1, characterized in that: During the ball milling process of step S1 and step S3, zirconium oxide ball mill and anhydrous ethanol are mixed, and the ratio of powder, ball mill and anhydrous ethanol is 1:2:
4.
3. A method for preparing sodium niobate-based dielectric ceramics according to claim 1 or 2, characterized in that: The ball milling method has a grinding speed of 400-600 rpm and a grinding time of 24-48 hours.
4. A method for preparing sodium niobate-based dielectric ceramics according to claim 1 or 2, characterized in that: The step S2 and step S3 are dried at 120° C., and the material in step S2 is passed through a 60-mesh sieve after drying.
5. The method for preparing sodium niobate-based dielectric ceramics according to claim 1, characterized in that: The initial heat preservation sintering in step S2 is specifically to place the steel sheet in a heat treatment furnace and sinter at 700-900° C. for 4 hours.
6. The method for preparing sodium niobate-based dielectric ceramics according to claim 1, characterized in that: The step S4 of secondary heat preservation sintering specifically includes heat preservation sintering in a sintering furnace at 1300-1400° C. for 2-4 hours.
7. The method for preparing sodium niobate-based dielectric ceramics according to claim 1, characterized in that: The three-time heat preservation sintering in step S5 specifically comprises heat preservation sintering in a sintering furnace at 400° C. for 0-30 minutes.
8. The method for preparing sodium niobate-based dielectric ceramics according to claim 6, characterized in that: The isostatic pressure of the isostatic pressing in step S4 is 200 MPa, and the holding time is 5 minutes.
9. The method for preparing sodium niobate-based dielectric ceramics according to claim 7, characterized in that: The ceramic fired in step S5 is ground to a thickness of 0.3 mm and then polished, and a silver layer with a thickness of 0.1±0.01 mm is plated on the surfaces of both sides of the ceramic piece.
10. A method for preparing sodium niobate-based dielectric ceramics according to claim 1, 8 or 9, characterized in that: In the step S4, the powder after drying is cooled and isostatically pressed into a cylindrical block, and in the step S5, the fired ceramic is ground thin and polished, and silver-plated and sintered into a silver-plated ceramic disc.
Citation Information
Patent Citations
Cubic sodium niobate ceramic dielectric material for ceramic capacitor and preparation method of cubic sodium niobate ceramic dielectric material
CN117088687A
Lead-free sodium niobate-based antiferroelectric ceramic with high saturated polarization and low residual polarization and preparation method thereof
CN109809815A
Energy storage efficiency enhanced high-energy storage lead-free ferroelectric ceramic material and preparation method thereof
CN112919907A
Sodium niobate-based lead-free antiferroelectric ceramic material with typical double ferroelectric hysteresis loops and preparation method of sodium niobate-based lead-free antiferroelectric ceramic material
CN116332643A